If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 7(8x + -5) + 12x = 0 Reorder the terms: 7(-5 + 8x) + 12x = 0 (-5 * 7 + 8x * 7) + 12x = 0 (-35 + 56x) + 12x = 0 Combine like terms: 56x + 12x = 68x -35 + 68x = 0 Solving -35 + 68x = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '35' to each side of the equation. -35 + 35 + 68x = 0 + 35 Combine like terms: -35 + 35 = 0 0 + 68x = 0 + 35 68x = 0 + 35 Combine like terms: 0 + 35 = 35 68x = 35 Divide each side by '68'. x = 0.5147058824 Simplifying x = 0.5147058824
| 2X^2+X=.44 | | e^5-3x=510 | | (3/8)/40=9/y | | 3+1/4*1-4/5 | | F=G*m*M/r^2 | | x+2*x+2=4 | | 8cos^2x=2 | | (3+1/4)(1-4/5) | | 5x^2+3x-.5=0 | | 49a^2-4=0 | | x^2-5x+6-0=0 | | H=5/3(a+2b) | | ln(x)=ln(x+6)-ln(3) | | 14-15+19=x-5 | | 14-15+19=33-5 | | 13a=13 | | ax-3c=5b | | 8x-4=5x+s | | 1/4k=4 | | 5=.5*16-3 | | x+4=.75x | | -4u-w=u+5w | | -16x/30=58/8 | | 7/(4x+2)=6/(5x+3) | | 3x+4y=73 | | 3x^3+20x^2-6x+7=0 | | 3a+4c=73 | | 4x/8+12=20 | | 12.56= | | 9(1)+7y=14 | | x=1/2*16-3 | | .6666666667x-.5y=12 |